PENGARUH PAD DAN DAU TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI PROVINSI BENGKULU - Aprilia, Dinda Vita; Astuti, Hartiningsih (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.01.TAHUN.2025DO - 10.24843/EEB.2025.v14.i01.p04, 2025)
PAD and DAU are very influential on economic growth and community welfare in Regencies/Cities in Bengkulu Province. The research design used is a casual research design to analyze the relationship between PAD and DAU on economic growth and community welfare from 2013 to 2023 The living conditions of the community in Bengkulu in 2022 are in the category of human development at a moderate level. This research applies a quantitative method. The analysis technique used is multiple linear regression with secondary data used in this study coming from BPS and DJPK for 10 years from the period 2013 to 2023. The data was processed using SPSS. The sample used was 9 districts and 1 city in Bengkulu province. The results of the study show that economic growth is greatly influenced by DAU and PAD. DAU and PAD have an impact on the quality of life of the community. To increase HDI, economic growth policies are needed to focus more on programs health, education, job creation to increase people's income as a foundation to achieve a decent standard of living.